On the recuperation of postindustrial sites: an aesthetic analysis - Jonathan Maskit (Unité Mixte de Recherche 8504 Géographie-cités, 2009)
Environmental aesthetics has mostly concerned itself not with changing environments, but with appreciating them. While making sense of how we do and ought to appreciate environments, both natural and built, is surely of value, aesthetics’ normative function can also contribute to debates about how we ought to intervene in sites that have been altered by human activity. In what follows the author seeks to offer some conceptual clarification, reserving the term restoration for only one particular sort of intervention, while introducing two new terms, transformation and renovation, for others. He draws his conclusion from Herman Prigann’s work in Gelsenkirchen (Germany’s Ruhr Valley): Skuplturenwald Rheinelbe (Rheinelbe Sculpture Wood).